Theories for Radical Change : Key Texts from the Political Economy of Marx and Lenin - Das, Raju, (Social Sciences E-Books Online, Collection 2025, 2025)
This book is focused on production and its relations. It argues for the primacy of economic over extra-economic processes, and of production and production relations over other aspects of the economic realm. It explores how production relations of capitalism and imperialism fetter the development of the productive forces of nature and wage-labour and hinder state's ability to solve the problems produced by capitalism. It covers a wide range of political-economic issues including commodity production, class differentiation, fundamental traits of capitalist production (including its uneven and combined development), capitalist state, and the impoverishment of common people and their struggle against the capitalist mode of production.